2021
DOI: 10.1017/s1755773921000114
|View full text |Cite
|
Sign up to set email alerts
|

The partisan politics of employment protection legislation: Social democrats, Christian democrats, and the conditioning effect of unemployment

Abstract: Political parties are likely to hold differing views about employment protection legislation (EPL). While pro-welfare parties could support EPL, pro-market parties might focus on labour market deregulation. In this paper, we investigate empirically whether partisan politics, especially the government participation of Social democrats and Christian democrats, matter for EPL in 21 established OECD countries from 1985 to 2019. We show that during the golden age of the welfare state, the level of EPL was much high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…This holds especially true if one considers the differences which exist between centre-right party families. Extant research has for instance shown that Christian-democratic cabinets tend to decrease EPL less than their conservative or liberal right-wing counterparts (Emmenegger, 2011; Zohlnhöfer and Voigt, 2021). Specifically on the topic of minimum wages, right-wing parties might, as hypothesized by Meyer (2016), also support minimum wages for fiscal reasons.…”
Section: The Politics Of the Minimum Wagementioning
confidence: 99%
“…This holds especially true if one considers the differences which exist between centre-right party families. Extant research has for instance shown that Christian-democratic cabinets tend to decrease EPL less than their conservative or liberal right-wing counterparts (Emmenegger, 2011; Zohlnhöfer and Voigt, 2021). Specifically on the topic of minimum wages, right-wing parties might, as hypothesized by Meyer (2016), also support minimum wages for fiscal reasons.…”
Section: The Politics Of the Minimum Wagementioning
confidence: 99%
“…Indeed, Christian democrats have built cross-class alliances that integrate the working class by creating generous social insurance programs, while maintaining strong ties with Catholic unions (Kalyas and Van Kersbergen, 2010). Studies have confirmed that governments with Christian Democratic parties tend to provide more generous social transfers (Huber et al, 1993) and tend to deregulate less the labor market (Zohlnhöfer and Voigt, 2021) than other governments. Also, the rise of a post-materialist cleavage has created a division between mainstream right-wing parties such as conservative and liberal parties that still put emphasis on economic issues and radical right parties that put more emphasis on cultural issues such as immigration (Kriesi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%